Bring Out Your Dead : The Great Plague of Yellow Fever in Philadelphia in 1793 - Powell, J. H. (John Harvey), 1914-1971 (Book collections on Project MUSE., 1993)
In 1793 a disastrous plague of yellow fever paralyzed Philadelphia, killing thousands of residents and bringing the nation's capital city to a standstill. In this psychological portrait of a city in terror, J. H. Powell presents a penetrating study of human nature revealing itself. Bring Out Your Dead is an absorbing account, form the original sources, of an infamous tragedy that left its mark on all it touched.